Grape‐clustered polyaniline grafted with carbon nanotube woven film as a flexible electrode material for supercapacitors. Issue 33 (23rd June 2022) - Li, Bingjian; Liu, Shi; Xu, Xixi; Yang, Haicun; Zhou, Yinjie; Yang, Dan; Zhang, Yun; Li, Jinchun
Abstract: The continuously reinforced carbon nanotube woven film (CNWF) prepared via the floating catalytic chemical vapor deposition (FCCVD) was modified by mixed acid and vinyltrimethoxysilane (VTMS) respectively to obtain carbon nanotube woven film (CNWF@VTMS) grafted with CH2 CH group. A series of novel self‐supporting composite electrode materials (CNWF@VTMS/PANI) for supercapacitors were then prepared by in‐situ chemical oxidative polymerization of aniline in the presence of the CNWF@VTMS film substrate as a conductive network framework. The results showed that CNWF@VTMS/PANI14 flexible electrode with grape‐clustered structure exhibited the highest specific capacitance of 531.3 F/g and the highest energy density of 26.5 Wh/kg at the current density of 1 A/g. It could maintain 75.1% of the initial value at a high current density of 10 A/g. The excellent electrochemical cycle and the structural stability have been confirmed on the condition of the higher capacitance retention of 96.6% after 2000 times of galvanostatic charge/discharge, and the almost unchanged electrochemical performances after 300 times of bending and twisting. Meanwhile, the stronger interfacial bonding between CNWF and PANI endowed a higher tensile strength of 129.2 MPa. In this article, CNWF@VTMS/PANI14 composite electrode could be a potential application in the field of deformable supercapacitors. Abstract : Polyaniline (PANI) with the grape‐clustered structure was grafted on the surface of continuously reinforced carbon nanotube woven film (CNWF) via in‐situ chemical oxidative polymerization. The strong interfacial bonding between CNWF and PANI plays an important role in improving the long‐term stability of the electrochemical performance. It could be a potential application in the field of deformable supercapacitors.